Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Ayam Panggang Mami Nungky Pejaten - Muhammad Razzan Troverandi; Rangga Adhi Putra (INDO PUBLISHING, 2026)
This study examines the influence of product quality and service quality on customer satisfaction at Ayam Panggang Mami Nungky, Pejaten, a celebrity-based culinary MSME that has grown rapidly since its founding. While prior studies have examined these variables in conventional restaurants, none have addressed celebrity-based culinary MSMEs, where owner popularity may shape customer expectations differently. Using a quantitative approach, data were collected from 100 respondents selected through purposive sampling and analyzed with multiple linear regression. The instrument passed validity and reliability tests, and the regression model satisfied all classical assumption tests. Results show that product quality and service quality each have a positive and significant partial effect on customer satisfaction, and jointly explain 56.8% of its variance, while the remainder is attributable to factors outside the model. These findings indicate that customer satisfaction in celebrity-based culinary MSMEs remains fundamentally shaped by core operational quality rather than owner popularity alone, offering practical implications for maintaining consistency amid rapid business growth